Mechanical properties of the A356 aluminum alloy modified with La/Ce - E. Aguirre-De la Torre R. Perez-Bustamante J. CamariUo-Cisneros C.D. Gomez-Esparza H.M. Medrano-Prieto R. Martinez-Sanchez (Journal of rare earths, 2013)
The research of rare earths for the synthesis of materials with improved mechanical performance is of great interest when they are considered for potential applications in the automotive industry. In this regard, the effect on the mechanical properties and microstmcture of the automotive A356 aluminum alloy reinforced with 0.2 （wt.%） AI-6Ce-3La （ACL） was investigated. The ACL was added to the melted A356 alloy in the as-received condition and processed by mechanical milling. In the second route, the effect of the ACL processed by mechanical milling and powder metallurgy techniques was investigated, and compared with the results ob- tained from the A356 alloy strengthened with ACL in the as-received condition. Microstmctural properties were evaluated by means of X-ray diffraction in order to observe the solubility of Ce/La in the A1 matrix. In addition, electron microscopy was employed in or- der to investigate the effect of milling time on the size and morphology of La/Ce phase under milling process. Mechanical properties of the A356 alloy modified with ACL were measured by hardness and tensile test. For comparison unmodified specimens of the A356 were characterized according to the previous procedure. The microstructural and mechanical characterization was carried out in specimens alter solution and artificial aging. Observations in scanning electron microscopy indicated a homogeneous dispersion of La/Ce phases by using both routes; however, mechanical results, in the modified A356 alloy with the ACL in the as-received condi- tion, showed an improvement in the mechanical performance of the A356 alloy over that reinforced with the ACL mechanically milled.